If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6e(3x) = 8 Remove parenthesis around (3x) 6e * 3x = 8 Reorder the terms for easier multiplication: 6 * 3e * x = 8 Multiply 6 * 3 18e * x = 8 Multiply e * x 18ex = 8 Solving 18ex = 8 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Divide each side by '18x'. e = 0.4444444444x-1 Simplifying e = 0.4444444444x-1
| 4(t-9)+5t= | | -25p-6(2-5p)=2(p-2)-17 | | 9+3/4*8+2+7= | | F(x)=3sinX-1 | | -25p-6(3-5p)=2(p-2)-17 | | 5x+5=4x+30 | | (7x^3+y)(8x^3+7y^2)= | | w^2+6w-28=0 | | 7[x+3(6-x)]=2x+1 | | 0=16t^2+12t+40 | | -48-64-2= | | X^3-2x^2+x-36=0 | | 8(y-3)+7(y+2)=95 | | 4x^4+16x^2-20=0 | | 3n^2-11n-14=0 | | 2x^2+7x=4x | | -7-7+1= | | sqrt9x^4y^5/sqrt18xy^3 | | -1/4x=64 | | 2x+18+3x-4=54-3x+32 | | 126399.2163=1/3*b*124.9 | | -x+4y=27 | | 5(4a+5b)-3(a+7b)= | | (2w^2-5w-7)-(6w^2+4w-4)= | | k=-1+7x | | 8+2=10+x | | k=8x-1+-1x | | x=66+-0.5y | | (2w^2-5-7)-(6w^2+4w-4)= | | x^2+10x+25+y^2-10y+25=1 | | x+(x-18)+(y-18)=96 | | 2/3x=1/3 |